Ensuring the genetic diversity of potatoes - Bamberg, J.; Jansky, S.H.; Rio, A. del; Ellis, David (Burleigh Dodds Science Publishing Limited, 2018)
Preserving genetic diversity lies at the heart of improvements in breeding and resilience in potato cultivation. This chapter discusses the challenges, opportunities and recent accomplishments of potato gene banks in the areas of acquisition, classification, preservation, evaluation and distribution of genetic stocks and information, as well as offering a legal perspective on access to genetic materials. The chapter reviews routes for acquisition of potato genetic material, together with methods for its classification and preservation. The chapter also discusses the evaluation and enhancement of potato genetic material, before looking at issues of control and assess to minimise problems such as transmission of disease.